Full-range Fourier-domain optical coherence tomography based on Mach–Zehnder interferometer. (January 2020) - Zhang, Qiukun; Zhong, Shuncong; Lin, Jiewen; Chen, Weiqiang; Luo, Manting; Zhong, Jiangfeng; Yu, Yingjie; Peng, Zhike; Cheng, Shuying
Highlights: A FR-FDOCT was proposed based on Mach–Zehnder interferometer with a tilted mirror which could generate simultaneously a series of accurate phase-delay interference signal. FR-FDOCT is capable of acquiring artifact-free images by construction of both amplitude and phase of interferogram from multiple sets of phase-delay signals. The Mach–Zehnder interferometric structure with a tilted mirror in reference arm could actively promote the innovation and development of OCT technology. Abstract: We proposed a full-range Fourier-domain optical coherence tomography (FR-FDOCT) based on a Mach–Zehnder interferometer with a tilted mirror which could generate a series of accurate phase-delay interference signals simultaneously. The FR-FDOCT is capable of acquiring artifact-free images by the construction of both amplitude and phase of the interferogram from multiple sets of phase-delay signals. The Mach–Zehnder interferometer make the reference arm became single-way optical path which is more convenient to adjust the reference beam than the return-way optical path (which means the incident and reflected beams use the same optical path) of traditional systems. A series of phase-delay interference signals were simultaneously acquired by a home-made two-dimensional spectrometer when tilting the mirror in the reference arm. The technique was employed to measure an anterior chamber of a porcine eye with a high symmetric artifact suppression of more than 45 dB. The technology could achieve double-range images effectively without any additional scanning device. It could actively promote the innovation and development of OCT technology.